The Dynamics of Jember Sari Wedding Dress In Jember From 2005 To 2018 - Alifatul Inaayah; Sumarjono Sumarjono; Mohamad Na'im; Akhmad Ryan Pratama (History Education, University of Jember, 2021)
Jember Sari wedding dress is a original wedding dress of Jember regency. Jember Sari wedding dress consists of kebaya, beskap and jarit. The purpose of examining Jember Sari wedding dress is in order to mantain a regional wedding dress and preserve the existing culture. The result of the study is the apperarance motive of Jember Sari weding dress as follows; (1) Socio-cultural factors, due to the fusion process of Javanese and Madura culture. The Javanese and Madurese etnics coexisted in Jember, thereby the new culture is called â€œPandhalunganâ€ culture. One of the Pandalungan culture is the wedding dress of Jember Sari. (2) In 2003, HARPI